2019
DOI: 10.1111/jnc.14812
|View full text |Cite
|
Sign up to set email alerts
|

Spinal high‐mobility group box‐1 induces long‐lasting mechanical hypersensitivity through the toll‐like receptor 4 and upregulation of interleukin‐1β in activated astrocytes

Abstract: Intrathecal treatment with recombinant high‐mobility group box‐1 (rHMGB1) in naïve mice leads to a persistent and significantly decreased hind paw withdrawal threshold to mechanical stimuli, suggesting that spinal HMGB1 evokes abnormal pain processing. By contrast, repeated intrathecal treatment with anti‐HMGB1 antibody significantly reverses hind paw mechano‐hypersensitivity in mice with a partial sciatic nerve ligation (PSNL). By contrast, the cellular mechanism by which spinal HMGB1 induces neuropathic pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…There is also other evidence demonstrating the critical role of HMGB1 in abnormal pain processing. Intrathecal, intraplantar, and perineural injection of HMGB1 produced mechanical hypersensitivity ( 62 , 84 , 85 ). HMGB1 is a multifunctional protein that interacts with a variety of receptors.…”
Section: Tlr4/opioid Receptor Pathway Crosstalk Central Immune Signamentioning
confidence: 99%
See 1 more Smart Citation
“…There is also other evidence demonstrating the critical role of HMGB1 in abnormal pain processing. Intrathecal, intraplantar, and perineural injection of HMGB1 produced mechanical hypersensitivity ( 62 , 84 , 85 ). HMGB1 is a multifunctional protein that interacts with a variety of receptors.…”
Section: Tlr4/opioid Receptor Pathway Crosstalk Central Immune Signamentioning
confidence: 99%
“…HMGB1 is a multifunctional protein that interacts with a variety of receptors. Tolerance, hyperalgesia, and allodynia have been shown to involve HMGB1 activating the RAGE, TLR4, and TLR5 signaling pathways (60,61,84,86).…”
Section: Tlr4/opioid Receptor Pathway Crosstalk Central Immune Signaling and Opioid Analgesiamentioning
confidence: 99%
“…Interestingly, the HMGB1/TLR4 axis is also pro‐nociceptive in the spinal cord, since i.t. administration of HMGB1 or ds‐HMGB1 causes TLR4‐dependent mechanical hyperalgesia/allodynia (Agalave et al, 2014; Morioka et al, 2019). Likewise, visceral nociception appears to involve the HMGB1/TLR4 axis in the peripheral tissue, because intravesical infusion of ds‐HMGB1 produces TLR4‐dependent abdominal mechanical hypersensitivity, that is, referred hyperalgesia/allodynia, in mice (F. Ma et al, 2017).…”
Section: A Role Of Hmgb1 In Pain Processingmentioning
confidence: 99%
“…In 2001, it was reported for the first time that injection of HMGB1 around the sciatic nerve induced mechanical allodynia in rats [90]. Recently, increasing evidence has unveiled the pro-nociceptive role of HMGB1 in the peripheral tissue and spinal cord [16,18,29,80,89], and demonstrated that endogenous HMGB1 is involved in the pathogenesis of various types of intractable pain [11,15], including inflammatory pain [28,29,80], visceral pain [19,20,30,32], neuropathic pain [23,31,76,91,92], cancer pain [33], and post-stroke pain [34]. Endogenous HMGB1 also appears to play a key role in the development of CIPN in rats or mice treated with cancer chemotherapeutics, such as paclitaxel, oxaliplatin, and vincristine, considering the complete prevention of CIPN by inactivation of HMGB1 with HMGB1-nAb or TMα (Figure 2 and Table 1) [8][9][10][11].…”
Section: Involvement Of Endogenous Hmgb1 In the Development Of Pathological Pain Including Cipnmentioning
confidence: 99%